Analysing the aerodynamics of the fastest ever marathon (The Engineer, 2017)
In the early hours of Saturday May 6, at the Monza motor racing circuit in Italy, Eliud Kipchoge ran 26.2 miles in 2 hours and 25 seconds, beating the existing marathon world record by 2 minutes and 32 seconds. The run was the culmination of Nike's "Breaking 2" project, a two year program aimed at demonstrating that it is physically possible for a human to run a marathon in less than two hours. In order to determine just how much influence "aerodynamic trickery" had in getting Kipchoge within 26 seconds of the mythical 2 hour barrier, we decided to run a series of computational fluid dynamics using STAR-CCM+, which is part of Siemens` Simcenter portfolio of simulation tools.